STUDENTS’ RESPONSE TOWARDS THE TEACHERS’ APPROACH AND METHOD OF TEACHING - Hanifi, Rusydi; Rahayu, Puji Sri (LET: Linguistics, Literature and English Teaching Journal, 2014)
This research is aimed (1) to know how the teachers differentiate teaching method for the students based on their language learning abilities (2) it is intended to investigate the specific approaches that the teachers use to motivate the students to learn English and (3) to know the students? response towards the teachers? method of teaching. To collect the data, the researchers applies triangulation techniques. This means that he makes a collaboration of several techniques of collecting data. They are classroom observation, interview with the classroom teachers, and questionnaire for the students.  The result showed that teachers apply different teaching method and have specific approaches to their students such as: letting their students have questions during or after class, helping their students individually, engaging their students in active participation during classroom activities either individually or in groups, etc. The students gave different response to different approach the teachers applied.